Konsep dan Penerapan Ruang Wisata Budaya - Prakoso, Aditha Agung (CV. Kurnia Grup, 2024)
Culture is one of the local resources that can be a tourist attraction for domestic and even foreign tourists. The cultural tourism attraction has a competitive advantage because it has uniqueness and distinctiveness that are different in each region. Besides that, cultural tourism can provide new knowledge and experience, which is the essence of the growing trend of quality tourism today. However, cultural tourism space as a media for expression and preservation of local culture is still not clearly explained, so the application and development of cultural tourism space, especially in Indonesia, is still not optimal and has a direct impact on society and its environment. This research aims to explain in detail the concept and application of cultural tourism spaces as a forum for community expression, cultural preservation, and economic impact. This research uses a literature review method to be able to explain the concept of cultural tourism space in the context of Indonesia so that a description of the concept and how the application of cultural tourism space can be used as a guide to the development of cultural tourism space in the context of Indonesia can be produced.